Determination of the optimal range of the compressor inlet air temperature in a power plant with stig cycle through of advanced exergetic analysis (2019)
Conventional exergy analysis identifies the more inefficient components; however, this doesn’t regard interaction between components, neither real improvement potential to each component of the system, this information is providing for the advanced exergy analysis. In this paper was developed an advanced exergy analysis to determine the optimal range of the compressor inlet air temperature, to compensate the power loss in a power plant with Stig cycle and an air cooling system. This plant without cooling system at ISO conditions produce 52 MW, while in local conditions (32 °C, 80%RH) its productions decreases to 44.3MW. The results showed that for every degree centigrade that the air temperature decreases at inlet compressor the power output increases in 0.17 MW and total destroyed exergy increases 0.23 MW. It was determined that for the optimal range of compressor inlet air temperature is between 10 and 12°C; at this range were obtained the highest power output values, and the values of the avoidable and endogenous exergy destroyed are diminished in 0.28 MW and 0.20 MW respectively compared to those given in local operating conditions. Copyright © 2019 ASME.